Invasions but Not Extinctions Change Phylogenetic Diversity of Angiosperm Assemblage on Southeastern Pacific Oceanic Islands - Castro-Morales, S (Public Library of Science, 2017)
We assessed changes in phylogenetic diversity of angiosperm flora on six oceanic islands located in the southeastern Pacific Ocean, by comparing flora from two periods: the pre-European colonization of islands and current times. We hypothesize that, in the time between these periods, extinction of local plant species and addition of exotic plants modified phylogenetic-α-diversity at different levels (deeper and terminal phylogeny) and increased phylo-β-diversity among islands. Based on floristic studies, we assembled a phylogenetic tree from occurrence data that includes 921 species, of which 165 and 756 were native or exotic in origin, respectively. Then, we studied change in the phylo-α-diversity and phylo-β-diversity (1 –Phylosor) by comparing pre-European and current times. Despite extinction of 18 native angiosperm species, an increase in species richness and phylo-α-diversity was observed for all islands studied, attributed to introduction of exotic plants (between 6 to 477 species per island). We did not observe significant variation of mean phylogenetic distance (MPD), a measure of the ‘deeper’ phylogenetic diversity of assemblages (e.g., orders, families), suggesting that neither extinctions nor introductions altered phylogenetic structure of the angiosperms of these islands. In regard to phylo-β-diversity, we detected temporal turnover (variation in phylogenetic composition) between periods to flora (0.38 ± 0.11). However, when analyses were performed only considering native plants, we did not observe significant temporal turnover between periods (0.07 ± 0.06). These results indicate that introduction of exotic angiosperms has contributed more notably than extinctions to the configuration of plant assemblages and phylogenetic diversity on the studied islands. Because phylogenetic diversity is closely related to functional diversity (species trait variations and roles performed by organisms), our results suggests that the introduction of exotic plants to these islands could have detrimental impacts for ecosystem functions and ecosystem services that islands provide (e.g. productivity). © 2017 Carvallo, Castro. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.